Tanggung Jawab Pemerintah Daerah di Kalimantan Timur Terhadap Fasilitas bagi Penyandang Disabilitas - Suwardi Sagama; Muzayyin Ahyar (FENOMENA, 2020)
The existence of facilities and infrastructure are important parts of achieving justice in the community. The issue of justice so far has talked a lot about issues of infrastructure for people with disabilities. This study aims to examine normatively how the responsibilities of the East Kalimantan regional government in providing facilities in public spaces for people with disabilities. This research basically begins with a normative legal study which examines a behavior from the perspective of the prevailing legal norms. The focus of this research is aimed at examining the existence of normative local government responsibilities. Furthermore, the researchers explored social facts related to the provision of facilities for people with disabilities in East Kalimantan, especially in Samarinda. This study found the responsibility of local governments regarding the provision of facilities for disabilities with the issuance of Peraturan Daerah Nomor.1 of 2018 concerning the Protection and Fulfillment of the Rights of Persons with Disabilities. The results of this study confirm that with the existence of Law Nomor 8 of 2016, local governments are the party responsible for fulfilling the rights of persons with disabilities. In addition, this study also indicates the existence of supporting and inhibiting factors in the implementation of the fulfillment of facilities for persons with disabilities.